2001
DOI: 10.1007/s004200000212
|View full text |Cite
|
Sign up to set email alerts
|

Review of the factors associated with musculoskeletal problems in epidemiological studies

Abstract: This inventory identifies the factors or categories of factors that were generally taken into consideration. It makes it possible also to evaluate the strength of the association with a given factor, in considering the number of studies finding an association, and those that did not consider this factor. Based on this review, some factors taken into consideration (such as weight or hobbies) could be excluded in further studies, and replaced by more specific psycho-organisational factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
148
2
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(167 citation statements)
references
References 19 publications
9
148
2
4
Order By: Relevance
“…For example, their jobs involve prolonged standing and they are frequently exposed to manual handling tasks, such as lifting, carrying, pushing and pulling. These activities have been previously identified as risk factors for musculoskeletal symptoms 5,8,9) . In addition, the role of psychosocial factors in the development and persistence of musculoskeletal symptoms in workers is well recognized 4,5,[10][11][12] .…”
Section: Abstract : B I O P S Y C H O S O C I a L F A C T O R mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, their jobs involve prolonged standing and they are frequently exposed to manual handling tasks, such as lifting, carrying, pushing and pulling. These activities have been previously identified as risk factors for musculoskeletal symptoms 5,8,9) . In addition, the role of psychosocial factors in the development and persistence of musculoskeletal symptoms in workers is well recognized 4,5,[10][11][12] .…”
Section: Abstract : B I O P S Y C H O S O C I a L F A C T O R mentioning
confidence: 99%
“…These activities have been previously identified as risk factors for musculoskeletal symptoms 5,8,9) . In addition, the role of psychosocial factors in the development and persistence of musculoskeletal symptoms in workers is well recognized 4,5,[10][11][12] . Salespersons inevitably encounter various psychosocial problems involving aspects of the work content, organization and interpersonal relationships.…”
Section: Abstract : B I O P S Y C H O S O C I a L F A C T O R mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrogoniometry also provides the opportunity to collect data on the length of time that the wrist is placed at cer angles. This is valuable information since one of the potential risk factors for developing symptoms of the forearm and/or wrist is working in constrained an extreme postures for long periods of time (Bernard, 1997;Marcus et al, 2002;Sluiter et al, 2001;Viikari-Juntura and Silverstein, 1999).. R wrist and forearm symptoms (Malchaire et al, 2001). It has been sugges risk increases with exposure to both extreme postures and repetitive movements (Bernard, 1997).…”
Section: Muscle Activitymentioning
confidence: 99%
“…Psychosocial factors are becoming an integral part of recent epidemiologic studies on WRMDs as identified by the National Institute of Occupational Safety and Health and the Research Council and Institute of Medicine [15], [21]. In the late 1990s and early 2000s, several epidemiological studies presented evidence for associations between WRMDs andseveral physical, psychosocial and individual factors [23], [24]. In the early 1990s, studies have focused on psychosocial factors of decision latitude and lack of co-worker support as factors contributing to upper-extremity WRMDs [25].…”
Section: Introductionmentioning
confidence: 99%